2006
DOI: 10.1016/j.nima.2005.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Multipass beam breakup in energy recovery linacs

Abstract: This paper is a compilation of several presentations on multipass beam breakup (BBU) in energy recovery linacs (ERLs) given at the 32nd Advanced ICFA Beam Workshop on ERLs. The goal of this paper is to summarize the progress achieved in analytical, numerical, and experimental studies of the instability and outline available and proposed BBU mitigation techniques. In this paper, a simplified theory of multipass BBU in recirculating linacs is presented. Several BBU suppression techniques and their working princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…33) The other limitation of electron beam current, instability at the recirculation, is dominated by beam break-up due to higher-order modes excited in superconducting cavities. 34) The threshold current of the beam break-up depends on the design of superconducting cavities and electron beam optics of the recirculation loop. Superconducting accelerator cavities for the efficient damping of higher-order modes are under development for ERLs that can be operated at average currents over 100 mA.…”
Section: System Performance 1 Gamma-ray Fluxmentioning
confidence: 99%
“…33) The other limitation of electron beam current, instability at the recirculation, is dominated by beam break-up due to higher-order modes excited in superconducting cavities. 34) The threshold current of the beam break-up depends on the design of superconducting cavities and electron beam optics of the recirculation loop. Superconducting accelerator cavities for the efficient damping of higher-order modes are under development for ERLs that can be operated at average currents over 100 mA.…”
Section: System Performance 1 Gamma-ray Fluxmentioning
confidence: 99%
“…For a more complete introduction to these beam optical techniques, the reader is referred to Refs. [2,[15][16][17][18].…”
Section: Bbu Suppression: Beam Optical Controlmentioning
confidence: 99%
“…The measurements are described in Ref. [30]. It has been observed that the threshold current can be predicted in cases where the accelerator is limited to currents below threshold for technical reasons.…”
Section: Article In Pressmentioning
confidence: 99%